Efektivitas Model Pembelajaran Diferensiasi pada Materi Struktur Teks Fabel dalam Meningkatkan Hasil Belajar Siswa Sekolah Dasar - Salma Naura M; Ibnu Muthi (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
The Indonesian language curriculum in elementary schools is fundamental in fostering students’ literacy skills, particularly in reading and writing narrative texts such as fables. Despite its importance, students often encounter difficulties in understanding the structural elements of fables—namely, orientation, complication, resolution, and coda. These challenges are frequently exacerbated by variations in students’ readiness, interests, and learning profiles, which are not sufficiently addressed by conventional, one-size-fits-all teaching methods. This study adopts a qualitative library research approach to examine theoretical foundations and prior empirical studies related to differentiated instruction in the context of fable text learning. The findings suggest that differentiated instruction, by modifying content, process, product, and learning environment, effectively enhances students’ comprehension and performance in fable text structure. Furthermore, this approach aligns with the principles of the Merdeka Curriculum, which emphasizes learner-centered and inclusive education. Thus, differentiated instruction presents a promising pedagogical strategy for elementary school teachers in improving Indonesian language learning outcomes.